2016
DOI: 10.1038/srep37297
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorylated form of FTY720 activates PP2A, represses inflammation and is devoid of S1P agonism in A549 lung epithelial cells

Abstract: Protein phosphatase 2A (PP2A) activity can be enhanced pharmacologically by PP2A-activating drugs (PADs). The sphingosine analog FTY720 is the best known PAD and we have shown that FTY720 represses production of pro-inflammatory cytokines responsible for respiratory disease pathogenesis. Whether its phosphorylated form, FTY720-P, also enhances PP2A activity independently of the sphingosine 1-phosphate (S1P) pathway was unknown. Herein, we show that FTY720-P enhances TNF-induced PP2A phosphatase activity and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…FTY720 treatment prevented enhanced MC degranulation after OVA treatment (Figure A). FTY720 can be phosphorylated in vivo to activate S1PR2 and repress inflammation . FTY720 did not alter skin S1P perhaps because of its inhibitory effect on Sgpl1 that results in S1P increase (Figure B).…”
Section: Resultsmentioning
confidence: 95%
“…FTY720 treatment prevented enhanced MC degranulation after OVA treatment (Figure A). FTY720 can be phosphorylated in vivo to activate S1PR2 and repress inflammation . FTY720 did not alter skin S1P perhaps because of its inhibitory effect on Sgpl1 that results in S1P increase (Figure B).…”
Section: Resultsmentioning
confidence: 95%
“…In vivo, FTY720 is phosphorylated by the enzyme sphingosine kinase 2 to form FTY720-phosphate, which resembles sphingosine 1-phosphate (36). FTY720 and its phosphorylated form have been used to activate PP2A both in vivo and in vitro (37). As seen in Fig.…”
Section: Pp2a But Not Ppp1 Dephosphorylates Tfe3 At Ser-321mentioning
confidence: 99%
“…Previous studies have shown that, PP2A dephosphorylates and activates GSK‐3β (Ivaska et al, ; Lin et al, ). Furthermore, FTY720 was known to activate PP2A in various types of cancer cells (Rahman et al, ; Yang, Huang, Lu, Li, & Huang, ). Therefore, we investigated the effect of FTY720 on GSK‐3β activation and we found that FTY720 dephosphorylated GSK‐3β expression.…”
Section: Resultsmentioning
confidence: 99%
“…Fingolimod (FTY720), is a strong immunosuppressor that has been approved by the US Food and Drug Administration (FDA) to treat relapsed multiple sclerosis (Cohen et al, ). FTY720 possess anticancer activity in multiple myeloma, hepatocellular carcinoma, gastric cancer, ovarian cancer, lung cancer, and colorectal cancer (Hung et al, ; Liao et al, ; Rahman et al, ; Zhang et al, ; Zheng et al, ). Currently it is being uses to treat multiple sclerosis (Montalban et al, ).…”
Section: Introductionmentioning
confidence: 99%